2021
DOI: 10.1007/s10049-021-00859-z
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitskompetenz und Notfallverhalten

Abstract: Zusammenfassung Hintergrund Die Anzahl an Patienten in Notaufnahmen steigt seit Jahren an. Im Besonderen wächst der Anteil an Patienten mit einem nichtdringlichen Behandlungsbedarf. Bislang ist unklar, ob dies in Deutschland auch auf eine eingeschränkte Gesundheitskompetenz zurückgeführt werden kann. Ziel der Arbeit Ziel der Studie war es, die Gesundheitskompetenz (GK) von Notfallpatienten mit nichtdringlichem Behandlungsbedarf zu erfassen, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
2
8
1
2
Order By: Relevance
“…The leaflet aimed to address previously identified health literacy deficiencies in low-acuity ED presenters. 9 10 37 38 Concordant with our sample’s composition, an observational study by Steenwinkel et al 39 found younger age and migration background associated with a greater need to receive information at the ED, which has been supported by research from the Netherlands 10 and Switzerland. 40 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The leaflet aimed to address previously identified health literacy deficiencies in low-acuity ED presenters. 9 10 37 38 Concordant with our sample’s composition, an observational study by Steenwinkel et al 39 found younger age and migration background associated with a greater need to receive information at the ED, which has been supported by research from the Netherlands 10 and Switzerland. 40 …”
Section: Discussionsupporting
confidence: 86%
“…Reasons for low-acuity ED visits are diverse and decision-making processes complex. Determinants of such consultations include a lack of knowledge about care alternatives,9 10 perceived difficulties in scheduling PC appointments,11 shortages of timely appointments in the ambulatory care sector,12 but also the comparable convenience of the ED 13. In Germany, patients can visit EDs at their own discretion without having to first consult a general practitioner (GP), call a hotline or follow any other gate keeping procedure.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results do not show differences in urgency perceptions by migration background of respondents. A recent study reported an association between lower health literacy and higher perceived urgency of treatment in emergency department patients [44]. Although an association between higher educational level and higher health literacy or emergency literacy was found [45,46], our findings indicate no differences in perceived urgency by the respondents' educational level when other characteristics of the respondents as well as of the vignettes were adjusted.…”
Section: Discussion Of Resultscontrasting
confidence: 76%
“…In Bezug auf das Verhalten bei Notfällen scheint eine unzureichende Gesundheitskompetenz von Bedeutung zu sein, wobei sich Defizite insbesondere bei der Einschätzung der richtigen Versorgung bei nichtdringlichen Hilfeersuchen zeigen. Anhand einer Umfrage konnte gezeigt werden, dass gerade Patientinnen und Patienten mit inadäquater Gesundheitskompetenz eher eine zentrale Notaufnahme als den kassenärztlichen Bereitschaftsdienst aufsuchen würden, weiterhin ist auch die hausärztliche Anbindung bei diesen Patientinnen und Patienten schlechter [69].…”
Section: Resilienzsteigerung Der Bevölkerungunclassified